Answer:
a = 4, b = 3
Step-by-step explanation:
7a = 28
a = 4
5(4) - 2b = 14
2b = 6
b = 3
<u><em>Note:</em></u>
<em>Your question is a little unclear. But, from my understanding, I assume you may be asking the evaluation of the expression 36x - y when x = 3 and y = -6.</em>
<em>so I will solve based on my assumption which anyways would clear your concept.</em>
Answer:
The value of 36x - y when x = 3 and y = -6 will be: 114
Step-by-step explanation:
Given
Assuming the expression
36x - y
To Determine
Evaluate 36x - y when x = 3 and y = -6
Given the expression
substitute x = 3 and y = -6 to evaluate the expression
Therefore, the value of 36x - y when x = 3 and y = -6 will be: 114
Answer:
i belive its 100
Step-by-step explanation: